THE USE OF QUIPPER SCHOOL AS AN ONLINE LEARNING MEDIUM: - Pertiwi, Rasyita; Jabu, Baso; Samtidar, Samtidar (State University of Makassar, 2022)
This research aims to find out students’ perception towards the use of Quipper School as an online learning medium and what are the advantages and disadvantage of Quipper School as a learning medium. This research applied a descriptive qualitative method. The data collection in this research was conducted by interviewing 30 students of SMAN 8 Makassar as the participants of this study. The result of this research found that there are several pluses such as: Free access video, show the right answer after the wrong one, ready to study material, easy to use and understand, concise and complete video explanation, has a feature that support the students to train their self with the tasks, quiz, and summary, and repeatable answer. For the minuses, the minuses of this application are network problem, pictures problem, freeze or bug, unclear explanations, and language problem. It can be concluded that Quipper School is easy to access and use, cost free, and useful for support online learning. Keywords—Quipper School, Students Perception